INVENTARISASI JENIS DAN TINGKAT KESEHATAN POHON PELINDUNG DI KOTA PALU, SULAWESI TENGAH - Hendro Hendro; Miswan Miswan; Ramadhanil Pitopang (Biocelebes, 2017)
Developing a green open space by planting shade trees is an effort to evolve artificial ecosystem in urban areas. The aim of this study was toinventory the species of shade trees and their health condition in Palu city. This study was held during period of June until August 2015 at several street in Palu city. Parameter observed were depth of the wound to stem diameters of the trees and the number of damaged parts of the stem. The result showed that the highest damage precentage was at Munif Rahman street, on Johar (Senna seamea Lamk) species with 9,67 % depth of wound and 23,19 % damage parts of the stem.